The Development of a Disease Is Not Contagious in Thailand - Kiatisuk Wongsaroj (GoAcademica Research & Publishing, 2020)
Over the past three decades, the public health landscape in Thailand has shifted remarkably. Currently chronic non-communicable diseases represent the largest cause of mortality in the Thai population. In light of the current situation, this paper synthesizes what is known about the chronic non-communicable disease situation in Thailand and analyzes current policy responses. Relevant contextual factors such as socio-economic transitions, health systems development, and health workforce capacities are also considered. Primary data for this study were collected by a review of policy documents, government statements, and statistics reported by the Thailand Ministry of Public Health. Secondary data were obtained by a thorough review of the existing literature. The paper finds that while current policy responses to chronic non-communicable diseases in the health sector have focused on improving prevention and control of risk factors, a stronger emphasis on chronic disease treatment and management may be needed in the future. The paper concludes with an exploration of the potential for developing and implementing realistic public health responses to the growing burden of chronic non-communicable diseases in a Southeast Asian country context by utilizing existing capacities in research, policy, and health workforce development.